Subire la violenza, ripensare la vulnerabilità: riflessioni su guerra, pace e comunità - Manzione, Claudia (Filosofia, 2023)
The aim of this paper is to reflect on war, starting from a reconsideration of the notions of force and vulnerability. The goal is not to deny toutcourt the dimension of conflict, but to affirm that it is not only through force and a hypothetical consequent state of war that it is possible to find a solution. The American philosopher Judith Butler, in Precarious Lives, underlines how human beings are subject to the violence of the others. If violence inhabits our lives, we should understand in which way we react to it; if force appears to be the only viable way or if there are new ways, different terms and further forms in which it is possible to remain in a dimension of conflict. We discuss – in a gender perspective – that Feminism gave the possibility to consider differently in which ways we can exercise power on the others.